(untitled) (Community Based Medical Journal, 2014)
Thyroid carcinoma is common and represents 1% of all human neoplasia. Incidence increases if occult carcinoma are taken into consideration. Some of the cancers of the thyroid gland have got relationship with non-neoplastic conditions such as Hashimoto thyroiditis, Graves’ disease and multinodular goiter. This cross sectional study was performed on a total of 50 cases of thyroid carcinoma at the Department of Pathology Bangabandhu Sheikh Mujib Medical University, Dhaka for a period of six months from March 2012 to August 2012 for histopathological evaluation of tumor and non-tumorous areas of thyroid gland. The age range of patients with malignant thyroid tumor was 12 to 65 years with a male to female ratio 1:3.2. Lymphocyte infiltration and lymphoid follicle formation were the predominant changes in the non-tumorous areas adjacent to thyroid malignancy which are found mostly with papillary thyroid carcinoma. This study suggested that if these changes are found in thyroid specimen which are operated due to any cause including clinically benign cases, we should thoroughly search for thyroid carcinoma inside the gland. CBMJ 2014 July: Vol. 03 No. 02 P: 09-14